1992
DOI: 10.1136/adc.67.11.1330
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effects of sodium valproate and carbamazepine in epilepsy.

Abstract: The result showed that both drugs were effective in most cases at modest dosage without causing notable psychological effects 12 months into treatment. Modest and temporary adverse cognitive effects seen earlier in treatment could have been the result of uncontrolled seizure discharge. Improved function was the same in children with epilepsy and controls. Some psychological abnormalities in the children with epilepsy were evident before treatment suggesting early unwanted effects of the epileptic process itsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
3

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 27 publications
6
53
0
3
Order By: Relevance
“…Several researchers have concluded that attentional disturbance in these children is the result of the epileptic process itself. Epilepsy and its underlying causes have been postulated to have more negative effects on cognition and behavior than the AEDs used for treatment (9,13,26).…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have concluded that attentional disturbance in these children is the result of the epileptic process itself. Epilepsy and its underlying causes have been postulated to have more negative effects on cognition and behavior than the AEDs used for treatment (9,13,26).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, conclusions about medication effects should not be deduced from these comparisons. 32,33 Improperly controlled between-subject comparisons were even found in studies that also included well-designed within-subject comparisons. 20,21,23 Again, conclusions drawn from these between-subject comparisons are spurious.…”
Section: Lack Of Equivalency In Groups Comparedmentioning
confidence: 99%
“…31,32 Stores et al examined intelligence, focused and sustained attention, memory, visual search ability, and visuomotor coordination in a group of 63 children with newly diagnosed epilepsy. 33 Performance on cognitive measures was assessed at pretreatment and 1, 3, 6, and 12 months after introduction of treatment. A control group of 47 neurologically normal children was included in the study.…”
Section: Carbamazepinementioning
confidence: 99%
“…55 In one Class II study, 15 of 163 children assigned to AED withdrew because of intolerable side effects, 56 and in another, children taking PB did not show an expected increase in IQ on retest. 57 In three other studies, which included 48 children taking VPA, 1 taking PHT, and 51 taking CBZ, evidence was not seen of behavioral or cognitive impairment [58][59][60] (see table 5). A report from the American Academy of Pediatrics 44 regarding general recommendations for awareness of behavioral and cognitive effects of AED noted that high blood levels of some AED (PHT, PB, primidone) were significantly related to cognitive decline.…”
Section: What Are the Nature And Frequency Of Side Effects Of Aed Commentioning
confidence: 99%